Plant genetic resources and food security: Stakeholder perspectives on the international treaty on plant genetic resources for food and agriculture - Frison, C.; López, F.; Esquinas-Alcazar, J.T. (Routledge, 2011)
The International Treaty on Plant Genetic Resources for Food and Agriculture provides a route map for the use of such resources for sustainable agriculture and food security. This book shows that despite conflicting interests among players in the global food chain, they managed to come to an agreement for the sake of improving global food security and efforts towards hunger alleviation.